Mesoscale ionospheric plasma irregularities and scintillation over Svalbard - van der Meeren, Christer (Journal of Geophysical Research: Space Physics, 2016)
This thesis investigates how navigation signals are compromised by ionospheric plasma irregularities in the auroral and polar ionosphere over Svalbard. In 2013, four multiconstellation global navigation satellite system (GNSS) receivers were installed in NyÅlesund, Longyearbyen, Hopen, and Bjørnøya. These receivers provide unprecedented coverage of scintillation and plasma density (total electron content) in the region. The four research papers in this thesis are detailed case studies investigating mesoscale irregularities and scintillation.We use data from these GNSS receivers, all-sky imagers, coherent and incoherent scatter radars, ionosondes, and in-situ satellite measurements. Paper I [van der Meeren et al., 2014] investigates scintillation and irregularities on the front of a tongue of ionization (TOI) in the polar cap. Moderate scintillation and structuring is observed on the leading edge of the TOI. We employ a novel method where we use spectrograms of the phase of raw GNSS signals to show that the structuring is real and not due to erroneous data detrending of the σφ phase scintillation index. Paper II [Oksavik et al., 2015] investigates irregularities in the dayside auroral region, specifically in relation to poleward-moving auroral forms (PMAFs). Scintillation is strongly localized to these intense and transient features, even in the presence of polar cap patches. Paper III [van der Meeren et al., 2015] investigates scintillation from substorm auroral emissions as polar cap patches enter the nightside auroral oval. The most severe scintillation is found when the auroral precipitation coincides with polar cap patches. The scintillation is strongly localized to signals intersecting intense auroral emissions. Paper IV [van der Meeren et al., 2016] investigates irregularities during quiet geomagnetic conditions. We find weak irregularities in relation to a stable and intense transpolar arc, but no scintillation is seen. The main results in this thesis are: Scintillation-producing irregularities can exist ...